Local tumor microbial signatures and response to checkpoint blockade in non-small cell lung cancer. (1st January 2021) - Boesch, Maximilian; Baty, Florent; Albrich, Werner C.; Flatz, Lukas; Rodriguez, Regulo; Rothschild, Sacha I.; Joerger, Markus; Früh, Martin; Brutsche, Martin H.
ABSTRACT: In cancer patients, the clinical response to checkpoint-based immunotherapy is associated with the composition and functional quality of the host microbiome. While the relevance of the gut microbiome for checkpoint immunotherapy outcome has been addressed intensively, data on the role of the local tumor microbiome are missing. Here, we set out to molecularly characterize the local non-small cell lung cancer microbiome using 16S rRNA gene amplicon sequencing of bronchoscopic tumor biopsies from patients treated with PD-1/PD-L1-targeted checkpoint inhibitors. Our analyses showed significant diversity of the tumor microbiome with high proportions of Firmicutes, Bacteroidetes and Proteobacteria. Correlations with clinical data revealed that high microbial diversity was associated with improved patient survival irrespective of radiology-based treatment response. Moreover, we found that the presence of Gammaproteobacteria correlated with low PD-L1 expression and poor response to checkpoint-based immunotherapy, translating into poor survival. Our study suggests novel microbiome-specific/derived biomarkers for checkpoint immunotherapy response prediction and prognosis in lung cancer. In a broader sense, our data draw attention to the local tumor microbial habitat as an important addition to the spatially separated microbiome of the gut compartment.